Biorregionalização da vegetação da Mata Atlântica e sua relação com fatores ambientais - Cantidio, Luiza Soares (2019)
The identification of ecological regions (ecoregions) by means of objective methods is the ideal approach to put the spatial delineation of metacommunities into practice and thus to obtain a better understanding of the distribution patterns of biota in the macro scale. Despite being the second largest forest complex in South America, there is so far no objective ecoregion scheme, based on the species composition of the Atlantic Forest flora. The current state of conservation of the Atlantic forest combined with its high rates of endemism qualify it as one of the main hotspots of biodiversity worldwide and point to the urgency of mapping its ecoregions. We propose a regionalization scheme for the Atlantic Forest, developed from cluster analysis on occurrence and abundance data of the domain flora species, and then investigated the influence of environmental factors on the patterns found. Our analyzes identified 14 and 21 ecoregions for abundance and occurrence data, respectively. The Atlantic Forest ecoregions are grouped into two large zones, in the north-south direction. Human impact, elevation, climate and edaphic variables were the main drivers of the observed configurations. Our ecoregions scheme provides a better understanding of the patterns of species distribution in the Atlantic Forest, the impact of the factors affecting it, and also provides a starting point for the planning and implementation of conservation actions.